\(\left(x-2\right)^2-\left(x-3\right)\left(x+3\right)=9\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 9 2018

a) \(\left(x+3\right)\left(x^2-3x+9\right)-x\left(x-2\right)\left(x+2\right)=27\)

\(\Rightarrow x^3+3^3-x\left(x^2-4\right)=27\)

\(\Rightarrow x^3+27-x^3+4x=27\)

\(\Rightarrow27+4x=27\)

\(\Rightarrow4x=0\)

\(\Rightarrow x=0\)

20 tháng 9 2018

b) \(2x^2+7x+3=0\)

\(\Rightarrow2x^2+x+6x+3=0\)

\(\Rightarrow x\left(2x+1\right)+3\left(2x+1\right)=0\)

\(\Rightarrow\left(2x+1\right)\left(x+3\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}2x+1=0\\x+3=0\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}2x=-1\\x=-3\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\x=-3\end{matrix}\right.\)

2 tháng 8 2017

1. (3x - 5)2 - (3x + 1)2 = 8

=> (3x - 5 - 3x - 1)(3x - 5 + 3x + 1) = 8

=> -6(6x - 4) = 8

=> 6x - 4 = \(\dfrac{-4}{3}\)

\(\Rightarrow x=\dfrac{4}{9}\)

2) 2x(8x - 3) - (4x - 3)2 = 27

=> 16x2 - 6x - 16x2 + 24x - 9 = 27

=> 18x - 9 = 27

=> x = 2

3) (2x - 3)2 - (2x + 1)2 = 3

=> (2x - 3 - 2x - 1)(2x - 3 + 2x +1) = 3

=> -4(4x - 2) = 3

=> 4x - 2 = \(\dfrac{-3}{4}\)

\(\Rightarrow x=\dfrac{5}{16}\)

4) (x + 5)2 - x2 = 45

=> (x + 5 - x)(x + 5 + x) = 45

=> 5(2x + 5) = 45

=> 2x + 5 = 9

=> x = 2

5) (x - 3)3 - (x - 3)(x2 + 3x + 9) + 9(x + 1)2 = 18

=> x3 - 9x2 + 27x - 27 - x3 + 27 + 9(x2 + 2x + 1) = 18

=> -9x2 + 27x + 9x2 + 18x + 9 = 18

=> 45x + 9 = 18

=> 45x = 9

=> x = \(\dfrac{1}{5}\)

6) x(x - 4)(x + 4) - (x - 5)(x2 + 5x + 25) = 13

=> x (x2 - 16) - (x3 - 125) = 13

=> x3 - 16x - x3 + 125 = 13

=> -16x = -112

=> x = 7.

2 tháng 8 2017

Bạn ơi có chắc đúng ko đấy.

a: \(\Leftrightarrow x^3-27-x\left(x^2-4\right)=1\)

\(\Leftrightarrow x^3-27-x^3+4x=1\)

=>4x-27=1

hay x=7

b: \(\Leftrightarrow x^3-9x^2+27x-27-x^3+27+6\left(x+1\right)^2+3x^2=15\)

\(\Leftrightarrow-9x^2+27x+6x^2+12x+6+3x^2=15\)

=>39x+6=15

hay x=3/13

c: \(\Leftrightarrow x^3-3x^2+3x-1-x^3-27+3x^2-12=2\)

\(\Leftrightarrow3x-40=2\)

hay x=14

28 tháng 9 2019

a)\(\left(x-1\right)^3+3\left(x+1\right)^2=\left(x^2-2x+4\right)\left(x+2\right)\)

\(\Leftrightarrow x^3-3x^2+3x-1+3\left(x^2+2x+1\right)=x^3+8\)

\(\Leftrightarrow-3x^2+3x+3x^2+6x+3=9\)

\(\Leftrightarrow9x=6\Leftrightarrow x=\frac{2}{3}\)

b) \(x^2-4=8\left(x-2\right)\)

\(\Leftrightarrow x^2-4=8x-16\)

\(\Leftrightarrow x^2-8x+12=0\)

\(\Leftrightarrow x^2-2x-6x+12=0\)

\(\Leftrightarrow x\left(x-2\right)-6\left(x-2\right)=0\)

\(\Leftrightarrow\left(x-6\right)\left(x-2\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-6=0\\x-2=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=6\\x=2\end{cases}}\)

28 tháng 9 2019

c) \(x^2-4x+4=9\left(x-2\right)\)

\(\Leftrightarrow\left(x-2\right)^2=9\left(x-2\right)\)

\(\Leftrightarrow\left(x-2\right)^2-9\left(x-2\right)=0\)

\(\Leftrightarrow\left(x-2\right)\left(x-11\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\x-11=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=11\end{cases}}\)

d) \(4x^2-12x+9=\left(5-x\right)^2\)

\(\Leftrightarrow\left(2x-3\right)^2=\left(5-x\right)^2\)

\(\Leftrightarrow\orbr{\begin{cases}2x-3=5-x\\2x-3=x-5\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{8}{3}\\x=-2\end{cases}}\)

a) Ta có: \(\left(x-3\right)\left(x^2+3x+9\right)\)

\(=\left(x-3\right)\left(x^2+x\cdot3+3^2\right)\)

\(=x^3-3^3=x^3-27\)

b) Ta có: \(\left(x-2\right)\left(x^2+2x+4\right)\)

\(=\left(x-2\right)\left(x^2+x\cdot2+2^2\right)\)

\(=x^3-2^3=x^3-8\)

c) Ta có: \(\left(x+4\right)\left(x^2-4x+16\right)\)

\(=\left(x+4\right)\left(x^2-x\cdot4+4^2\right)\)

\(=x^3+4^3=x^3+64\)

d) Ta có: \(\left(x-3y\right)\left(x^2+3xy+9y^2\right)\)

\(=\left(x-3y\right)\left[x^2+x\cdot3y+\left(3y\right)^2\right]\)

\(=x^3-\left(3y\right)^3=x^3-27y^3\)

e) Ta có: \(\left(x^2-\frac{1}{3}\right)\left(x^4+\frac{1}{3}x^2+\frac{1}{9}\right)\)

\(=\left(x^2-\frac{1}{3}\right)\left[\left(x^2\right)^2+x^2\cdot\frac{1}{3}+\left(\frac{1}{3}\right)^2\right]\)

\(=\left(x^2\right)^3-\left(\frac{1}{3}\right)^3\)

\(=x^6-\frac{1}{27}\)

f) Ta có: \(\left(\frac{1}{3}x+2y\right)\left(\frac{1}{9}x^2-\frac{2}{3}xy+4y^2\right)\)

\(=\left(\frac{1}{3}x+2y\right)\left[\left(\frac{1}{3}x\right)^2-\frac{1}{3}x\cdot2y+\left(2y\right)^2\right]\)

\(=\left(\frac{1}{3}x\right)^3+\left(2y\right)^3\)

\(=\frac{1}{27}x^3+8y^3\)